Alternative Characteristics Analysis of Mixture Oil Transformer using Breakdown Voltage Method - Yahya, Muhammad Amri; Prasetyo, Tegar; Hermialingga, Septi; Putri Manurung, Nancy Eka (DPTE FT UNY, 2023)
This research shows the effect of oil mixture and temperature on breakdown voltage. Palm oil is combined with diala-b oil in various mix ratios and various temperatures. Test results on the sample, as the concentration of the mixture of diala-b oil increases, the breakdown voltage value also increases. The breakdown voltage values of all oil mixture samples that have gone through the treatment process have met the IEC standard No. 56 of 1991 with results that are classified as above the standard (standard â‰¥ 30kV/2.5mm). Breakdown voltage values for the composition of 100% diala-b oil, 100% palm oil, and a mixture of 50% diala-b oil: 50% palm oil at 60 °C, 70 °C, 80 °C, 90 °C, and 100 °C is above the standard that is â‰¥ 30 kV. Water content and acidity affect the breakdown voltage value. Based on the results of breakdown voltage testing that has been done, palm oil can be used as an alternative to transformer oil.